STUDI MEMORI KOLEKTIF: PERANG PADERI DI NAGARI MATUA HILIA - -, Novia Rahmadani (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2025)
This research discusses the Paderi War in the collective memory of the people of Nagari Matua Hilia. The focus of the problem is how the events of the Paderi War in Nagari Matua Hilia are remembered and inherited in the collective memory of the local community. This research uses a local history perspective, and prioritizes the role of oral history in shaping people's understanding of the past. This research uses historical research methods, which include heuristics, source criticism, synthesis, and historiography. The results showed that the collective memory of the Nagari Matua Hilia community was built through: first, material relics such as the Pincuran Gadang Mosque; second, toponymy, such as Labuang XX; third, local archives. In addition, collective memory collective memory has formed a shared identity that inherits the spirit of the ancestors' struggle of the ancestors in the face of Dutch colonialism. awareness awareness of this history fosters a sense of community responsibility to preserve the remaining historical heritage as a source of knowledge for future generations. This research also emphasizes the importance of collective memory in local history in local history as an effort to maintain cultural identity and enrich regional historiography.